Uncovering Biological Factors That Regulate Hepatocellular Carcinoma Growth Using Patient‐Derived Xenograft Assays. Issue 3 (2nd September 2020) - Zhu, Min; Li, Lin; Lu, Tianshi; Yoo, Hyesun; Zhu, Ji; Gopal, Purva; Wang, Sam C.; Porembka, Matthew R.; Rich, Nicole E.; Kagan, Sofia; Odewole, Mobolaji; Renteria, Veronica; et al.
Abstract : Background and Aims: Several major factors limit our understanding of hepatocellular carcinoma (HCC). First, human HCCs are infrequently biopsied for diagnosis and thus are not often biologically interrogated. Second, HCC initiation and progression are strongly influenced by the cirrhotic microenvironment, and the exact contributions of intrinsic and extrinsic tumor factors are unclear. A powerful approach to examine the personalized biology of liver cancers and the influence of host tissues is with patient‐derived xenograft (PDX) models. In Asia, HCCs from patients with hepatitis B virus have been efficiently converted into PDXs, but few parallel efforts from the west have been reported. Approach and Results: In a large‐scale analysis, we implanted 93 HCCs and 8 cholangiocarcinomas (CCAs) to systematically analyze host factors and to define an optimized platform for PDX development from both surgical and biopsy samples. NOD Scid IL‐2Rγ −/− (NSG) mice that had undergone partial hepatectomy (PHx) represented the best combination of engraftability, growth, and passageability, but overall rates were low and indicative of a unique intrinsic biology for HCCs in the United States. PDX models preserved the histology and genetic features of parental tumors, and ultimately, eight models were usable for preclinical studies. Intriguingly, HCC PDXs were differentially sensitive to regorafenib and sorafenib, and CCA PDXs were also highly sensitive to regorafenib. Conclusions: PDX models functionalize early and advanced stage HCCs and revealed unique biological features of liver cancers from the United States.